PERAN GURU MEMOTIVASI BELAJAR IPS MATERI SUMBER DAYA ALAM DAN PEMANFAATANNYA KELAS IV DI SD NEGERI 200107 PADANGSIDIMPUAN - Sikumbang, Disti Melati; Siregar, Khoiruddin Saleh; Siregar, Royhanun; Sabri, Sabri (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This study aims to determine the role of the teacher as a motivator in motivating social studies learning natural resources material and its utilization for class IV at SD Negeri 200107 Padangsidimpuan. The type of research used is descriptive qualitative research. The informants in this study were the homeroom teacher of class IV as the main informant and the students of class IV as key informants. Data collection techniques used in this study were: 1) observation, 2) interviews, and 3) documentation. Based on the results of the study, it can be concluded that the role of the homeroom teacher for class IV as a motivator at SD Negeri 200107 Padang Sidempuan in motivating learning Social Sciences natural resource material and its utilization has been carried out to the fullest extent possible by making students active in teaching and learning activities, applying effective and innovative learning methods, helping students to be able to develop their potential optimally, help students if they experience problems or difficulties, get to know and build good relationships with students. This can be seen by giving special attention to students and providing opportunities for students to actively participate in asking questions, providing interesting learning, making learning active to emphasize the learning process, creating a new learning atmosphere, and providing motivation to students to be enthusiastic in participating. learning. Teachers have also done their best by being a good example in the classroom.   Keywords:The Role of the Teacher, Motivating Social Studies Learning, Natural Resource.   Abstrak Penelitian ini bertujuan untuk mengetahui peran guru sebagai motivator dalam memotivasi belajar IPS materi sumber daya alam dan pemanfaatannya kelas IV Di SD Negeri 200107 Padangsidimpuan.Jenis penelitian yang digunakan adalah penelitian kualitatif deskriptif.Informan adalah penelitian ini adalah wali kelas IV sebagai informan utama dan siswa kelas IV sebagai informan kunci. Teknik pengumpulan data yang dugunakan dalam penelitian ini adalah : 1) observasi, 2) wawancara,  dan 3) dokumentasi.  Berdasarkan hasil penelitian dapat disimpulkan peran guru wali kelas IV sebagai motivator di SD Negeri 200107 Padangsidimpuan dalam memotivasi belajar IPS materi sumber daya alam dan pemanfaatannya sudah dilakukan semaksimal mungkin dengan membuat siswa aktif dalam kegiatan belajar mengajar, menerapkan metode pembelajaran yang efektif dan inovatif, membantu siswa untuk dapat mengembangkan potensi secara optimal, membantu siswa jika mengalami kendala atau kesulitan, mengenal dan membangun hubungan yang baik dengan siswa. Hal ini terlihat dengan memberikan perhatian khusus terhadap siswa dan memberi kesempatan kepada siswa untuk berpartisipasi aktif bertanya, menyediakan pembelajaran yang menarik, membuat pembelajaran manjadi aktif untuk menekankan pada proses pembelajaran, menciptakan suasana belajar yang baru, serta adanya memberikan motivasi kepada siswa agar bersemangat dalam mengikuti pembelajaran. Guru juga sudah melakukan secara maksimal dengan menjadi contoh yang baik di dalam kelas. Kata Kunci: Peran Guru, Memotivasi Belajar IPS, Sumber Daya Alam.